Delivering genomic medicine in the UK National Health Service: a systematic review and narrative synthesis - Pearce, C; Goettke, E; Hallowell, N; McCormack, P; Flinter, F; McKevitt, C (Springer Nature, 2019)
Purpose: We sought to assess the readiness of the United Kingdom (UK) National Health Service to implement a Genomic Medicine Service. We conducted a systematic literature review to identify what is known about factors related to the implementation of genomic medicine in routine health care and to draw out the implications for the UK and other settings. Methods: Relevant studies were identified in Web of Science and PubMed from their date of inception to April 2018. The review included primary research studies using quantitative, qualitative, or mixed methods, and systematic reviews. A narrative synthesis was conducted. Results: Fifty-five studies met our inclusion criteria. The majority of studies reviewed were conducted in the United States. We identified four domains: (1) systems, (2) training and workforce needs, (3) professional attitudes and values, and (4) the role of patients and the public. Conclusion: Mainstreaming genomic medicine into routine clinical practice requires actions at each level of the health-care system. Our synthesis emphasized the organizational, social, and cultural implications of reforming practice, highlighting that demonstration of clinical utility and cost-effectiveness, attending to the compatibility of genomic medicine with clinical principles, and involving and engaging patients are key to successful implementation.